2022
DOI: 10.1097/pg9.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Impact of COVID-19 on Job Prospects and Training for Pediatric Gastroenterology Fellows in North America

Abstract: Objectives: As the COVID-19 pandemic persisted into the 2020 to 2021 academic year, there was a continued effect on graduate medical education trainees and graduating trainee job attainment. Our survey aims to investigate how the pandemic has continued to affect job search and attainment for pediatric gastroenterology fellows as well as to re-evaluate the pandemic’s impact on pediatric gastroenterology fellow educational experiences. Methods: An anonymous survey was distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A few studies looked at the impact of COVID-19 on job aspects for pediatric gastroenterology fellows. 93 First jobs were chosen with fewer geographic restrictions, less negotiation over salary, less reported overall satisfaction with their selected position, and less interest in researchdominant positions. 82 In fact, the study reported journals.sagepub.com/home/tag…”
Section: Career Decisionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies looked at the impact of COVID-19 on job aspects for pediatric gastroenterology fellows. 93 First jobs were chosen with fewer geographic restrictions, less negotiation over salary, less reported overall satisfaction with their selected position, and less interest in researchdominant positions. 82 In fact, the study reported journals.sagepub.com/home/tag…”
Section: Career Decisionsmentioning
confidence: 99%
“…A few studies looked at the impact of COVID-19 on job aspects for pediatric gastroenterology fellows. 71 , 92 94 Sanchez et al. reported that when pediatric gastroenterology fellows applied for jobs during COVID-19, they focused on job attainment rather than other factors.…”
Section: Career Decisionsmentioning
confidence: 99%
See 1 more Smart Citation